2022
DOI: 10.1002/eom2.12183
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ growth of ultrathin sulfur microcrystal on MXene‐based 3D matrice for flexible lithium–sulfur batteries

Abstract: Lithium–sulfur batteries (Li‐S batteries) are promising next‐generation energy storage systems because of their high‐theoretical energy density. However, the commercialization of Li‐S batteries is still impeded by the aggregation of sulfur, low‐sulfur utilization, shuttling of dissolved polysulfides and sluggish reaction kinetics. Herein, we designed a hierarchically maple leaf‐like structured sulfur electrodes by in‐situ growth of ultrathin sulfur microcrystal on two‐dimensional MXene‐graphene‐cellulose nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Once the challenges are mastered, commercial availability could be expected around year 2035. From material research, Li-S battery based on S-carbon nanofibers [38] and MXene-graphene-cellulose nanofiber matrice cathodes [39] have been proposed, showing a maximum specific capacity of around 1200 mAh/g and stable cycling for several hundreds to several thousands of cycles.…”
Section: Future: Gen 5 Batteriesmentioning
confidence: 99%
“…Once the challenges are mastered, commercial availability could be expected around year 2035. From material research, Li-S battery based on S-carbon nanofibers [38] and MXene-graphene-cellulose nanofiber matrice cathodes [39] have been proposed, showing a maximum specific capacity of around 1200 mAh/g and stable cycling for several hundreds to several thousands of cycles.…”
Section: Future: Gen 5 Batteriesmentioning
confidence: 99%
“…It can be concluded that SACs can effectively enable the comprehensive management of suppression of the LiPS shuttle effect, promotion of sulfur reactions, and lithium metal anode optimization toward long‐life LSBs. An LSB system involves complex phase conversion reactions that result in unclear correlations between sulfur conversion and lithium evolution 122–126 . Therefore, identification of the working mechanism of SACs in lithium dissolution, and transfer and deposition behaviors is still an intractable challenge.…”
Section: Sac Strategy For Li–s Chemistrymentioning
confidence: 99%
“…Fe Fe-N Li foil [121] reactions that result in unclear correlations between sulfur conversion and lithium evolution. [122][123][124][125][126] Therefore, identification of the working mechanism of SACs in lithium dissolution, and transfer and deposition behaviors is still an intractable challenge.…”
Section: Mitigated Lithium Dendrite By Sacsmentioning
confidence: 99%
“…The flourishing market of electric vehicles requires increasing energy density, cyclic stability, and safety performance for energy storage devices. [1][2][3] However, the energy output of recent lithium-ion batteries (LIBs) is restricted by relatively low-energy densities of current commercial cathode materials such as LiCoO 2 , LiFePO 4 , and LiMn 1/3 Co 1/3 Ni 1/3 O 2 . [4,5] Lithium-rich layered oxides (LLOs) with an ultrahigh energy density of over 1000 Wh kg −1 and low cost are regarded as one of the most promising cathode materials for next-generation LIBs.…”
Section: Introductionmentioning
confidence: 99%